2021
DOI: 10.1039/d1cc00278c
|View full text |Cite
|
Sign up to set email alerts
|

C2-Selective silylation of pyridines by a rhodium–aluminum complex

Abstract: We have developed a C2-selective mono-silylation of a variety of pyridines using a Rh-Al complex. Both the site- and mono-selectivity are controlled via the pyridine coordination to the Lewis- acidic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Heterobimetallic complexes comprised of a transition metal (TM) and a main group metal (MGM) are the focus of considerable interest because of the possibility that the disparate chemistry of the two partners could combine cooperatively to bring about the novel stoichiometric and/or catalytic activation of small molecules. In one recent example, shown in Scheme a, the challenging C–O activation of an anisole takes place across the Rh–Al bond of complex I to afford II , which upon addition of a silane, mediates catalytic C–O bond reduction . Complex I represents one class of heterobimetallic complexes in which the MGM forms part of a multidentate ligand on the TM center .…”
Section: Introductionmentioning
confidence: 99%
“…Heterobimetallic complexes comprised of a transition metal (TM) and a main group metal (MGM) are the focus of considerable interest because of the possibility that the disparate chemistry of the two partners could combine cooperatively to bring about the novel stoichiometric and/or catalytic activation of small molecules. In one recent example, shown in Scheme a, the challenging C–O activation of an anisole takes place across the Rh–Al bond of complex I to afford II , which upon addition of a silane, mediates catalytic C–O bond reduction . Complex I represents one class of heterobimetallic complexes in which the MGM forms part of a multidentate ligand on the TM center .…”
Section: Introductionmentioning
confidence: 99%
“…1 In the last few years new strategies have emerged for the C-H activation of pyridines that are based on cooperative action of transition metal and main group elements contained within a single reactive species. [2][3][4][5][6][7][8][9][10][11][12] Very recently, our group reported a well-defined Fe-Al complex that is capable of selectively breaking the sp 2 C-H bond of pyridine (Fig. 1).…”
mentioning
confidence: 99%
“…In addition, they found that a similar catalyst can also effectively facilitate a C2-H silylation of pyridines, providing a series of silylated heterocyles in up to 94% yield (Scheme 20) [31].…”
Section: Precious Metal Catalysismentioning
confidence: 99%